The optimum range of ocean and freshwater quality parameters - Md. Simul Bhuyan; Istiak Ahamed Mojumder; Monika Das (Annals of Marine Science - Peertechz Publications, 2020)
The optimum range of water is very important to determine the quality of water found in ocean and river. Standard is range is very crucial for researchers to know the absolute status of the ocean and river water quality [1-3]. Ocean and river are being polluted day by day. Industrialization, urbanization, oil dumping, and other development activities are responsible for this water quality deterioration.